Financial inclusion, financial education, and financial regulation: A story from Indonesia - Tulus Tambunan (Asian Development Bank Institute (ADBI), 2015)
Many reforms have taken place in Indonesia following the Asian financial crisis of 1997 - 1998. The government has embarked upon institutional transformation, making the country one of the region's most vibrant democracies. In social, economic, and political areas, Indonesia has seen much progress. Wide reforms have been carried out in all areas of governance, including in the financial sector, and a new development strategy has been adopted for "inclusive" economic development. This paper examines the shift in Indonesia's national economic development strategy from its "exclusive" orientation during the New Order era before the Asian financial crisis, to its "inclusive" orientation after the crisis. It also examines the impact the reforms have had on poverty reduction and the campaign to create a better environment for micro, small, and medium-sized enterprises (MSMEs). The constraints that Indonesia faces in implementing inclusive development, particularly financial inclusion, are also discussed.
Keywords: G21; G28; I25; 330